Traduire Cicéron au XVe siècle Le ›Livre des offices‹ d'Anjourrant Bourré V Édition critique - Delsaux, Olivier (CICERO, 2019)
In an article entitled "Per una nuova valutazione del Quattrocento francese" published in 1957 on the threshold of the first booklet of "Studi Francesi", Franco Simone affirmed that philological restitution of texts and understanding of their place inside the culture that had products were the premise essential, before any exegesis or critical interpretation, to achieve a redefinition of overly limited historiographical paradigms in which the French literature from the late Middle Ages had been located until that time. We know that the research of the Italian scientist has powerfully dissipated the historiographical myth of the 15th century Gothic opposed to the blooming of Italian culture, for the benefit of an enhancement of wealth and fertility a period which testifies, among other things, to an acute historical awareness and of great interest for the ancient tradition, as well as for the great founders of Italian Humanism; in the following decades, synergistic efforts specialists largely trained in French, Belgian and Italian schools have resulted in the publication of numerous studies and editions in the field of literature in French medium, in favor of the base for a imposing critical work that has refined, corrected and deepened the suggested perspective formerly by the author of La coscienza della rinascita negli umanisti francesi.